Complex polymer orientation. (8th November 2016) - Gilbert, P.H.; Giacomin, A.J.
Abstract: Previously, we explored the dynamics of a dilute suspension of rigid dumbbells as a model for polymeric liquids in large-amplitude oscillatory shear (LAOS) flow. We derived the expression for the polymer orientation distribution, and then we decomposed this function into its first five harmonics (the zeroth, first, second, third and fourth harmonics). In this work, we separate each harmonic into its components in-phase and out-of-phase with cos n ω t, and then use three-dimensional imaging to investigate complex polymer motion in LAOS. Our analysis focuses on the nonlinear viscoelastic regime, specifically, where both λω and λ γ ˙ 0 are unity. We learn that harmonic components, in-phase and out-of-phase with cosnωt, contribute to orientation differently, and that out-of-phase components tend to give more probable orientation away from the flow direction. We also find that some orientation contributions are caused by interferences between complex components, some constructive and some destructive. Graphical abstract: Highlights: Fourier decomposition of polymer orientation distribution for LAOS was examined. Three-dimensional imaging reveals harmonic contribution to orientation. Relative influence of orientation components governs dynamic harmonic behavior.